MicroRNA as potential biomarker for severity, progression, and therapeutic monitoring in animal models of limb-girdle muscular dystrophy: a systematic review - Oliveira, Mayala Thayrine de Jesus Santos; da Silva Santana, Talita Araújo Barbosa; Costa, Marcela Câmara Machado; Borges, Grasiely Faccin; de Miranda, Felipe Silva; Slaibi-Filho, José; Luiz, Wilson Barros; Campos, Luciene Cristina Gastalho (Frontiers in Cellular Neuroscience, 2023)
Limb-girdle muscular dystrophies (LGMD) constitute a heterogeneous group of neuromuscular disorders in which there are alterations in proteins responsible for the preservation of muscle architecture and function, leading to proximal and progressive muscle weakness. There is, however, significant phenotypic and genotypic variation, as well as difficulty in establishing biomarkers that help to define pathogenic mechanisms and assess disease severity and progression. In this field, there is special attention to microRNAs, small non-coding RNA molecules related to the regulation of gene expression and, consequently, the production of proteins. Thus, this research aimed to verify the correlation between the expression of microRNAs and the severity, progression, and therapeutic response of LGMD animal models. A search was carried out in the PubMed, Embase, Scopus, ScienceDirect, Cochrane, and SciELO databases, with articles in English and without a time limit. The PRISMA 2020 checklist was used, and the protocol of this review was submitted to PROSPERO. The bibliographic survey of the 434 records found that 5 original articles met the inclusion criteria. The studies explored myomicroRNAs or miRNA panels with gene expression analysis. The analysis demonstrates that miR-1, 133a, and 206 are differentially expressed in serum and muscle. They change according to the degree of inflammation, fibrosis, muscle regeneration, and progression of the dystrophic process. MicroRNAs are up-regulated in dystrophic muscles, which are reversed after treatment in a dose-dependent manner. The present study inferred that miRs are essential in severity, progression, and therapeutic response in LGMD models and may be a useful biomarker in clinical research and prognosis. However, the practical application of these findings should be further explored.